Lumbar lordosis morphology correlates to pelvic incidence and erector spinae muscularity - Yang Li (Nature Portfolio, 2021)
Abstract The retrospective study aimed to investigate the relationship between lumbar lordosis morphology, pelvic incidence and paraspinal muscle. It enrolled asymptomatic adult volunteers aged between 18 and 45 years old. Lumbar lordosis morphology, consisting of total lumbar lordosis (LL), proximal lumbar lordosis (PLL), distal lumbar lordosis (DLL), lumbar lordosis apex (LLA) and inflexion point, was evaluated, as well as pelvic incidence (PI) and muscularity of erector spinae (ES) and multifidus. Pearson correlation was performed to analyze the relationship between each other parameter. Cases were stratified according to pelvic incidence (very low < 30°, low 30°–45°, moderate 45°–60°, and high > 60°), comparison between groups was performed by univariance analysis. 87 asymptomatic adult volunteers (33 females and 54 males) were included in the study. PLL revealed a correlation with LLA (r = 0.603, p = 0.002) and inflexion point (r = 0.536, p = 0.004), but did not DLL with LL apex (r = 0.204, p = 0.058) or inflexion point (r = 0.210, p = 0.051). PI revealed a greater correlation with PLL (r = −0.673, p < 0.001) than with DLL (r = −0.237, p = 0.045). Linear stepwise regression analysis also exhibited the correlation between PI and PLL (R2 = 0.452, PLL = 16.2–0.61 * PI, p < 0.001). ES muscularity correlated with LL apex (r = −0.279, p = 0.014) and inflexion point (r = −0.227, p = 0.047). Stratification by PI demonstrated PLL increased across groups (p < 0.001), but DLL was comparable between low and moderate PI group (p = 0.329). Lumbar lordosis morphology appears to accommodate to pelvic incidence and erector spinae muscularity. Proximal lumbar lordosis has a bigger correlation with pelvic incidence than the distal lumbar lordosis. The results are helpful for restoring a rational lumbar lordosis shape in long fusion surgery.